Acceptance Behavior Theories and Models in Software Engineering - Börstler, Jürgen; Ali, Nauman bin; Petersen, Kai; Engström, Emelie (Blekinge Institute of Technology, 2023)
Electronic supplement for a mapping study on acceptance behavior theories and models in SE

Please refer to the following paper when you cite/use this data:

Jürgen Börstler, Nauman bin Ali, Kai Petersen, Emelie Engström (2024).Acceptance behavior theories and models in software engineering — A mapping study.Information and Software Technology.https://doi.org/10.1016/j.infsof.2024.107469

Overview of the electronic supplement

An overview-file (README.docx) comprising the following:

An overview of the supplements.

A plain list of the theories and models of acceptance behavior used for constructing the search string.

A plain list of the software engineering venues used for constructing the search string.

A ready-to-use search string for Scopus (plain text).

A plain list of the 47 included primary studies.

A separate Bibtex-file (p1-p47.bib) with all 47 included primary studies.

A separate Excel-file (data extraction.xlsx) comprising the following sheets:

The data extracted for the 47 included primary studies.

The 27 primary studies excluded during full-text reading and data extraction.
Keywords: Computer and Information Sciences; Data- och informationsvetenskap (datateknik)